25. THE SUSCEPTIBILITY OF STREPTOCOCCUS PNEUMONIAE TO ANTIBIOTICS AMONG CHILDREN TREATED AT THE NATIONAL CHILDREN’S HOSPITAL, 2020 (Vietnam Journal of Community Medicine, 2023)
Objectives: Streptococcus pneumoniae causes severe diseases with a high mortality rate. The studyaims to determine the susceptibility of Streptococcus pneumoniae to antibiotics among children aged< 5 years old at the National Children’s Hospital to find the most effective treatment.Study methods: The study was conducted in the laboratory with a descriptive research design.Results: Streptococcus was resistant to macrolides (> 95%), cotrimoxazole (90%), and clindamycin(95.3%). Multiple antibiotic resistance Streptococcus accounted for 64%. In addition, 100% ofStreptococcus were sensitive to rifampicin, linezolid and vancomycin, followed by amoxicillin(MIC90 = 2 µg/ml) at 95%, ceftriaxone (MIC90 = 4 µg/ml) at 61.1%, cefotaxime (MIC90 = 4 µg/ml) at57.4%, and penicillin G (MIC90=4 µg/ml) at 43.9%.Conclusions: Streptococcus was resistant to penicillins, cephalosporins, sulphonamides, andmacrolides. It was still sensitive to rifampin, glycopeptides, oxazolidinones, and quinolones.Therefore, the treatment of Streptococcus pneumoniae should be based on its antibiotic resistancepatterns to find the most sensitive antibiotic.
Keywords: Streptococcus, pneumoniae, children,MIC: minimum Inhibitory Concentration.